The Influence of Diode Laser Intensity Modulation on Photoacoustic Image Quality for Oral Soft Tissue Imaging: Influence of Laser Intensity on PA Image Quality - Widyaningrum, Rini; Gracea, Rellyca Sola; Agustina, Dewi; Mudjosemedi, Munakhir; Mitrayana, Mitrayana; Silalahi, Harry Miyosi (Journal of Lasers in Medical Sciences, 2020)
Introduction: Imaging technologies have been developed to assist physicians and dentists in detecting various diseases. Photoacoustic imaging is a new technique that shows great applicability to soft tissues. This study aimed to investigate the effect of diode laser intensity modulation on the photoacoustic image quality. Methods: The prototype of the PAI system in this study utilized a non-ionizing 532 nm continuous-wave diode laser illumination. Samples in this study were oral soft tissues of Sprague–Dawley rats fixed in 10% formalin solution. PA images were taken ex vivo by using the PAI system. The laser exposure for oral soft tissue imaging was set in various duty cycles. The samples were embedded in paraffin, and PA images were taken from the paraffin-embedded tissue blocks in a similar method by using duty cycles of 40%, 45%, 50%, 55%, 60% respectively to reveal the influence of the laser duty cycle on PA image quality. Results: The oral soft tissue is clearly shown as a yellow to red area in PA images, whereas the non-biological material appears as a blue background. The color of the PA image is determined by the PA intensity. Hence, the PA intensity of oral soft tissue was generally higher than that of the non-biological material around it. The Kruskal–Wallis test followed by Mann–Whitney post-hoc analysis revealed significant differences (P < 0.05) in the quality of PA images produced by using a 16%–47% duty cycle of laser intensity modulation for direct imaging of oral soft tissue fixed in 10% formalin solution. The PA image quality of paraffin-embedded tissue was higher than that of direct oral soft-tissue images, but no significant differences in PA image quality were found between the groups. Conclusion: The PAI system built in this study can image oral soft tissue...[Complete in Fulltext]